(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
This study is configured as an investigation into the historical, political, cultural and religious meanders of India before and after independence. These aspects constitute the beating heart and the soul of Midnight’s Children, the most celebrated work by Salman Rushdie’s narrative corpus and one of the milestones of the contemporary literary scene. The text of the Indian writer assumes the physiognomy of a modern epic, at times comic, of a magmatic and karstic text for those who appear to be foreign to the dynamics and atmospheres of a boundless and multicultural country like India itself. We are faced with a novel that, in its complex warping, escapes any kind of aesthetic and gender categorization, appealing to any stylistic-rhetorical resource, just to pursue its true objective: the unity in the diversity.